ECONOMIC VALUATION OF ECOSYSTEM SERVICES FOR THE MAINTENANCE OF TOURISM ACTIVITY IN THE CENTRAL AMAZON, BRAZIL - Soria-Díaz, Henry Francisco; Lima de Alencastro Graça, Paulo Maurício; Díaz-Salas, Simith Del Carmen; Chambi-Legoas, Roger; Leitão dos Reis, João Rodrigo; Soria-Solano, Benjamín (Floresta, 2024)
The valuation of ecosystem services provides essential information that makes it possible to estimate the economic value of environmental resources and their benefits. The aim was to estimate the value of the forest's cultural ecosystem services provided to maintain tourist activity in Presidente Figueiredo, Amazonas. The contingent valuation method (CVM) was used to estimate the willingness to pay (WTP) of users (tourists and visitors) and the willingness to accept (WTA) of landowners, local business owners and other interviewees. The results of the interviews indicate that 71% of users would be willing to pay an average of R$16.57 day-1visit-1, while 100% of interviewees would be willing to conserve the forests in exchange for receiving R$327.63 ha-1year-1. In conclusion, most of the interviewees agreed that valuing the forest's ecosystem services is fundamental to maintaining tourist activity.